The neuroprotective and anti-apoptotic effects of melatonin on hemolytic hyperbilirubinemia-induced oxidative brain damage - MEMİŞOĞLU, ASLI; YEGEN, BERRAK; ÖZEK, EREN; ŞİRVANCI, SERAP (WILEY, 2016)
Melatonin exerts protection in several inflammatory and neurodegenerative disorders. To investigate the neuroprotective effects of melatonin in an experimental hemolysis-induced hyperbilirubinemia, newborn Sprague-Dawley rats (25-40 g, n = 72) were injected with phenylhydrazine hydrochloride (PHZ; 75 mg/kg) and the injections were repeated at the 24th hour. Rats were treated with saline or melatonin (10 mg/kg) 30 min before the first and second PHZ injections and 24 h after the 2nd PHZ injections. Control rats (n = 24) were injected with saline, but not PHZ. At sixth hours after the last injections of saline or melatonin, all rats were decapitated. Tumor necrosis factor (TNF)-alpha, IL-1 beta, IL-10 and brain-derived neurotrophic factor (BDNF) and S100B levels in the plasma were measured. Brain tissue malondialdehyde (MDA), glutathione (GSH) levels and myeloperoxidase (MPO) activities were measured, and brain tissues were evaluated for apoptosis by TUNEL method. In the saline-treated PHZ group, hemoglobin, hematocrit levels were reduced, and total/direct bilirubin levels were elevated when compared to control group. Increased plasma TNF-alpha, IL-1 beta levels, along with decreased BDNF, S100B and IL-10 values were observed in the saline-treated PHZ group, while these changes were all reversed in the melatonin-treated group. Increased MDA levels and MPO activities in the brain tissues of saline-treated hyperbilirubinemic rats, concomitant with depleted brain GSH stores, were also reversed in the melatonin-treated hyperbilirubinemic rats. Increased TUNEL(+) cells in the hippocampus of saline-treated PHZ group were reduced by melatonin treatment. Melatonin exerts neuroprotective and anti-apoptotic effects on the oxidative neuronal damage of the newborn rats with hemolysis and hyperbilirubinemia.
Keywords: apoptosis; hemolysis; hyperbilirubinemia; melatonin; newborn; FETAL-RAT BRAIN; NF-KAPPA-B; NEUROTROPHIC FACTOR; UNCONJUGATED BILIRUBIN; WHITE-MATTER; SUBARACHNOID HEMORRHAGE; ALZHEIMERS-DISEASE; SIGNALING PATHWAYS; NERVOUS-SYSTEM; NEONATAL-RATS